Սիրոյ տեղը Յովհաննէսի Ա. թղթի աստուածաբանական համակարգում - Քէշիշեան, Էդուարդ Սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Первое послание Иоанна — это книга Нового Завета, в которой наиболее полно раскрывается тема любви. Современные исследователи Евангелия и по- сланий Иоанна по-разному трактуют и интерпретируют идею любви. Цель настоящей статьи — раскрыть богословское значение любви в Первом послании Иоанна, а также прояснить её взаимосвязь с другими разделами догматического богословия․ The First Epistle of John is a book of the New Testament that most fully reveals the theme of love. Contemporary scholars of the Gospel and the Epistles of John hold different views regarding the interpretation and meaning of love. The purpose of this article is to reveal the theological significance of love in the First Epistle of John, as well as to clarify its relationship with other branches of the dogmatic theology.
Keywords: Կրօնագիտական; Աստուածաբանական համակարգ